An Efforts to Develop Picture Stories for Gender Identity Recognition by Integrating Pancasila Student Profile for Students of Sekolah Indonesia Bangkok (SIB) Thailand: Efforts to Develop Picture Stories for Gender Identity Recognition by Integrating Pancasila Student Profile for Students of Sekolah Indonesia Bangkok (SIB) Thailand - Rezty Wijayaningputri, Arinta; Danawati, Murtyas Galuh; Mukhlishina, Innany (Jurnal Gentala Pendidikan Dasar, 2025)
This research aims to develop a picture story based on the Pancasila Student Profile as a learning medium in the introduction of gender identity to students of Sekolah Indonesia Bangkok (SIB) in Thailand. The problem behind this research is the lack of effective educational media in introducing the concept of gender identity in accordance with the values of Pancasila in an overseas school environment. The methodology used in this research is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, and questionnaires involving students, teachers, and material experts. The results showed that the developed picture stories were effective in improving students' understanding of gender identity and the value of the Pancasila Student Profile. These picture stories also received positive responses from teachers and students, indicating that this media can be an interesting and meaningful educational alternative. Thus, the development of picture stories based on the Pancasila Learner Profile is expected to be one of the solutions in introducing gender identity educationally and contextually in international schools.